Impact of the ESC 2021 guidelines on cardiac pacing and cardiac resynchronization therapy left bundle branch block definition on CRT patient selection and survival. (19th May 2022) - Rijks, J; Ghossein, M; Luermans, J; Maass, A; Meine, M; Prinzen, F; Linz, D; Vernooy, K; Van Stipdonk, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The recently published ESC 2021 guidelines on cardiac pacing and cardiac resynchronization therapy (CRT) underwent significant changes compared to the ESC 2013 guidelines regarding the definition of left bundle branch block (LBBB) by adding notching or slurring in 2 adjacent leads as a prerequisite. The level of recommendation for CRT depends on diagnosing LBBB or non-LBBB. These changes may have a significant impact on patient selection for CRT, as fewer patients may be diagnosed with LBBB and may therefore get a lower level of recommendation for CRT. Purpose: In this study we investigated the impact of these changes in LBBB definition on patient selection and heart transplantation/left ventricular assist device (LVAD) free survival. Methods: A large multicenter CRT database, consisting of consecutive patients implanted with a CRT device between 2001 and 2015 in 3 university hospitals in the Netherlands, was used for this study. Patient selection, device implantation, lead positioning and follow-up were according to then prevailing guidelines and local protocols. For this study, patients were selected with baseline sinus rhythm, QRS duration >130ms, and without right ventricular pacing. Patients were stratified according to ESC 2013 and ESC 2021 guideline definitions on LBBB. Results: The current analyses included 1.202 CRT patients. 66% of patients were male with an age of 66±11 years. Heart failure etiology was ischemic in 49% of patients with baseline left ventricular ejection fraction of 25% and baseline NYHA class II-III in 93% of patients. There is a considerable difference in LBBB diagnoses when stratifying patients according to ESC 2013 and ESC 2021 guideline definitions as especially the number of LBBB patients is reduced from 80.9% to 31.6% (Figure 1). Heart transplantation/LVAD free survival analyses when stratifying according to ESC 2013 LBBB definition showed significant separation of the curves (p<0.0001) (Figure 2). Furthermore, there was a significant difference between the wide (QRS>150ms) LBBB and wide non-LBBB subgroup concerning heart transplantation/LVAD free survival (p<0.0001). In contrast, there was no significant separation of the curves when stratifying according to ESC 2021 LBBB definition (Figure 2). Conclusion: The changes made in LBBB definition in the ESC 2021 CRT guidelines lead to a difference in stratification of LBBB and non-LBBB. The ESC 2013 LBBB definition, however, seems to be better in predicting heart transplantation/LVAD free survival after CRT.